Donor characteristics and risk of hepatocellular carcinoma recurrence after liver transplantation. Issue 10 (22nd June 2015) - Orci, L A; Berney, T; Majno, P E; Lacotte, S; Oldani, G; Morel, P; Mentha, G; Toso, C
Abstract: Background: To date, studies assessing the risk of post-transplant hepatocellular carcinoma (HCC) recurrence have focused on tumour characteristics. This study investigated the impact of donor characteristics and graft quality on post-transplant HCC recurrence. Methods: Using the Scientific Registry of Transplant Recipients patients with HCC who received a liver transplant between 2004 and 2011 were included, and post-transplant HCC recurrence was assessed. A multivariable competing risk regression model was fitted, adjusting for confounders such as recipient sex, age, tumour volume, α-fetoprotein, time on the waiting list and transplant centre. Results: A total of 9724 liver transplant recipients were included. Patients receiving a graft procured from a donor older than 60 years (adjusted hazard ratio (HR) 1·38, 95 per cent c.i. 1·10 to 1·73; P = 0·006), a donor with a history of diabetes (adjusted HR 1·43, 1·11 to 1·83; P = 0·006) and a donor with a body mass index of 35 kg/m 2 or more (adjusted HR 1·36, 1·04 to 1·77; P = 0·023) had an increased rate of post-transplant HCC recurrence. In 3007 patients with documented steatosis, severe graft steatosis (more than 60 per cent) was also linked to an increased risk of recurrence (adjusted HR 1·65, 1·03 to 2·64; P = 0·037). Recipients of organs from donation after cardiac death donors with prolonged warm ischaemia had higher recurrence rates (adjusted HR 4·26, 1·20 to 15·1; P = 0·025). Conclusion: Donor-related factors such as donor age, body mass index, diabetes and steatosis are associated with an increased rate of HCC recurrence after liver transplantation. Abstract : Donor characteristics are important